2021
DOI: 10.1371/journal.pone.0246967
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of vitamin C-treated induced-regulatory T cells on heart allograft rejection under vitamin C-deficient or –sufficient conditions

Abstract: Foxp3 stability of vitamin C-treated induced-regulatory T cells (V-iTregs) is superior to that of conventional iTregs (C-iTregs). However, the role of V-iTregs in allograft rejection under vitamin C-deficient conditions, such as those seen in humans, remains unclear. We aimed to elucidate the role of vitamin C treatment on generation and maintenance of iTregs from gulo knockout (Gulo-KO) mice as well as wild type (WT) mice, and in vitro and in vivo suppressive effects of V-iTregs on heart allograft rejection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Clinically relevant animal models of vitamin C (ascorbate) synthesis deficiency are essential for improving our understanding of the role of ascorbate in the pathogenesis of complex diseases . In this context, the Gulo –/– mouse is a relevant model to examine the impact of ascorbate on different biological processes in vivo . Importantly, the levels of ascorbate found in the serum of Gulo –/– mice will reflect the amounts of ascorbate provided in drinking water. Moreover, it was found that serum ascorbate concentrations showed a sigmoid-shaped dose–response curve similar to that observed in human studies. , By simply changing the amount of ascorbate in drinking water, we can control the concentration of ascorbate in the serum of these mice in a noninvasive manner and study its impact on different biological processes in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically relevant animal models of vitamin C (ascorbate) synthesis deficiency are essential for improving our understanding of the role of ascorbate in the pathogenesis of complex diseases . In this context, the Gulo –/– mouse is a relevant model to examine the impact of ascorbate on different biological processes in vivo . Importantly, the levels of ascorbate found in the serum of Gulo –/– mice will reflect the amounts of ascorbate provided in drinking water. Moreover, it was found that serum ascorbate concentrations showed a sigmoid-shaped dose–response curve similar to that observed in human studies. , By simply changing the amount of ascorbate in drinking water, we can control the concentration of ascorbate in the serum of these mice in a noninvasive manner and study its impact on different biological processes in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding Vitamin C: Comprehensive Examination of Its Biological Significance… DOI: http://dx.doi.org/10.5772/intechopen.114122 including mice, are capable of synthesizing vitamin C from glucose, while humans and other primates meet their daily requirements for it through their diet because they lack the L-gulono-g-lactone oxidase enzyme involved in vitamin C synthesis [14][15][16].…”
Section: Vitamin C: Chemical Structure and Synthesismentioning
confidence: 99%
“…95,96 In an allogeneic heart transplant model, however, iTreg cells differentiated in the presence or absence of VC similarly promoted the survival of heart allografts. 97 Therefore, the effect of VC on epigenome remodeling warrants further investigation to improve adoptive immune cell therapy, especially for specific immunosuppression.…”
Section: Animal Models Of Vc Deficiency and Vc Supplementationmentioning
confidence: 99%